HUMOR IN DEDDY’S CORBUZIER “SOMASI” - Flores, Priskalia D; Padji, Simon S; Sama, Gratiana (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2024)
The purpose of this study was to find out the forms of humor in a stand-up comedy video titled